KEBUTUHAN PENGEMBANGAN DIRI PEMULUNG DALAM RANGKA MENINGKATKAN TARAF HIDUP - Sigit Santoso (Jurnal Kependidikan, 2004)
Abstract This research is intended to find out (1) scavengers’ needs for self-development based indirectly on the fulfillment of physical needs, the needs for security, social needs, and the needs for self-esteem; (2) the relationship between scavengers’ knowledge about garbage and their needs for self-developments. This is a descriptive research using a causal study method with a sample of 200 persons taken randomly. The subjects of the research were scavengers, i.e. people whose work is to search useful materials among discarded or refused materials/ garbage living in the municipality of Surakarta. Two kinds of instruments were used in this research ; an instrument to reveal the needs for self-development consisting of 40 items (r=0.765), and one to reveal scavengers’ knowledge about garbage consisting of 36 items (r=0.773) and some other supplementary items. The data analyses used were path analysis and simple correlation technique. The results of the research remarked that (1) The needs for self-development was indirectly affected by the fulfillment of physiological needs, the needs of security, social needs, and the needs of self-esteem. This can be seen from the results of path analysis which showed that to reach the needs of self-development, the scavengers have to take some steps hierarchically, i.e. physically needs, the for security, social needs, and the needs of self-esteem. The results of path analysis showed that the coefficients resulted from their paths respectively were higher than those resulted from other paths: X1àX2 = 0.236, X2àX3 0.517, X3àX4= 0.437, and X4àY 0.363 (2)The relationship between  scavengers’ knowledge of garbage and their needs of self-development revealed by using a simple correlation showed the coefficient of correlation of 0.468 at the level of significance of 0.1 Keywords: scavengers’, self-development, self-concept